Pendekatan Metode Target Costing Pada Pendapatan Sewa Ruang Dalam Meningkatkan Laba Perusahaan Pada PT. Angkasa Pura 1 (Persero) Bandar Udara Sam Ratulangi Manado - Languju, Cicilya Vennesa; Morasa, Jenny; Budiarso, Novi (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2022)
Every company is required to be able to survive in achieving the company's goals that have been set. Target costing is the determination of the maximum possible cost for the manufacture of products and service producers which is expected to create profits with a predetermined maximum cost constraint. The purpose of this study was to evaluate the use of the target costing method in an effort to increase profits in space rentals that exist in the company at PT. Angkasa Pura 1 (Persero) Sam Ratulangi Airport Manado. PT Angkasa Pura 1 (Persero) is a State-Owned Enterprise (BUMN) within the Ministry of Transportation which always provides an optimal contribution to the state through airport operations and services. This research is a type of qualitative descriptive research. The results of the study are the profits generated at PT. Angkasa Pura 1 (Persero) Sam Ratulangi Airport Manado in 2020 with a target costing of Rp. 5,400,119,666., while the profit generated before using target costing was Rp. 4,928.079,722. Where can be seen an increase in profit of Rp. 472,039,944. after using target costing.Keywords: Target Costing, Income, Profit, Services, Space Rental